Effect of a Self-directed and Supervised Pulmonary Rehabilitation Approach on Cough and Sputum Expectoration in Chronic Obstructive Pulmonary Disease - Huma Balqias; Syed Alamdar Hussain; Usman Farooq; Umair Ahmad; Rohail Amir Babar (Lithuanian Sports University, 2022)
Background. Chronic obstructive pulmonary disease (COPD) is a multifactorial, progressive chronic lung disease. COPD was rated as the third largest cause of death by the World Health Organization (WHO) in 2016. Cough and sputum are present in about 60% of COPD patients. For persons with COPD who are unable to attend the standard centre-based program, home-based pulmonary rehabilitation offers a cost-effective option. The aim. To compare the effects of supervised and self-directed pulmonary rehabilitation on cough and sputum expectoration in patients with chronic obstructive pulmonary disease. Methods. Forty COPD-diagnosed subjects with ages between 40 to 60 years were recruited for this randomized clinical trial. The participants were randomly distributed into self-managed (n=18) and supervised (n=19) groups. Data was collected using a 6-minute walk test, the Leicester Cough Questionnaire and a cough and sputum assessment questionnaire at baseline after 6 weeks post treatment. Results. There was a significant difference found between self-managed and supervised groups for six-minute walk test with P value to be P > 0.005. While analysing LCQ, overall no significant difference was observed demonstrating between two groups with P > 0.05; besides, physical factors showed a significant difference during the pre-session which showed P = 0.004. No significant difference was found while analysing values from Cough and sputum assessment questionnaire with P > 0.05 Conclusion. Supervised exercise program and self-managed group show equal improvement in COPD patients. Self-management exercise should be encouraged for active involvement of patient during the treatment and to promote self-preventive behavior. Keywords: sputum, cough, self-management, pulmonary rehabilitation.